Do canto xamânico e outras histórias: leituras de The age of the Rainmakers, de Wilson Harris - Neiva, Gabriel Cambraia (2015)
This dissertation explores the four short narratives in The Age of the Rainmakers, by the Guyanese writer Wilson Harris (1971). It compares each fictional narrative with the indigenous textualities presented in travel literature and anthropological accounts of the area, often mentioned by the author in a preliminary note. It contextualises Wilson Harris' contribution and the particular book under study, by mapping Guyana's literary history and the specific place that this tradition holds as the only English-speaking, Caribbean country on the South American continent. Shaping the literary space of the Guianas, in which the forest and its indigenous peoples have a strong influence with their aesthetics and philosophy, this literature shows the transformational character of Amerindian mythology with a close relationship between environment and language. This is the encounter place of different cultures, where, creatively, new conceptual possibilities to think humanity are suggested, as the writer himself theorizes as cross-cultural imagination.